Decomposition of biodegradable plastic bags for kitchen waste collection in industrial composting - Sikander, Asma; Deegener, Stefan; Körner, Ina (Frontiers in Sustainable Food Systems, 2024)
With the growing awareness of microplastics in the environment, the question of microplastics as remnants of biodegradable plastic (BDP) products is gaining momentum. BDP bags for kitchen waste collection are often certified as fully compostable as proof of industrial compostability. Frequently certification is done using under standardized laboratory conditions within 12 weeks. Composting plants often process biowaste into compost in a shorter time under inhomogeneous conditions. This study investigates the decomposition behavior of commercially available BDP bags for kitchen waste collection at an industrial composting plant within a practically realistic time frame of 6 weeks. The research determines the decomposition behavior under practice conditions. Four bag types, two made from thermoplastic starch (TPS) blends and two from polylactic acid (PLA) blends underwent composting. The decomposition was evaluated by examining the remaining macro- (> 8 mm), meso- (2–8 mm), and microparticles (1–2 mm) in the compost with different methods. After 6 weeks, the mass-based decomposition rate of TPS blend bags exceeded 95%. In contrast, PLA blend bags failed to reach a decomposition rate of 90%. The study did not depict very small particles <1 mm. However, they are present. The study findings indicate that composting time and conditions, inhomogeneities, as well as the bag type are crucial factors influencing the decomposition of BDP bags. Concerns are raised about the usefulness of DIN 13432 as certification scheme for industrial conditions.